The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1002/(sici)1521-3757(19981002)110:19<2829::aid-ange2829>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Alkylierung von porösem Silicium durch direkte Umsetzung mit Alkenen und Alkinen

Abstract: Wasserstoff‐funktionalisiertes poröses Silicium (PS) ist gegenüber Alkenen und Alkinen für eine unkatalysierte Hydrosilylierung ausreichend reaktiv. Die dabei erhaltenen alkylmodifizierten PS‐Oberflächen weisen erheblich veränderte physikalische wie auch chemische Eigenschaften auf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our preferred method is thermal hydrosilation of alkenyl/alkynyl derivatives due to its functional group tolerance 71. 72 Alkylation of hydrogen‐terminated Si<111> ( Si‐H ) with 4,4′‐dimethoxytrityl‐protected ω ‐undecenol provides modified silicon surfaces ( Si‐C 11 ‐ODMT ) which, after detritylation, present a primary alcohol group suitable for on‐chip DNA synthesis 5. As a phosphoramidite, 1 was incorporated at the electrode surface as a monomer ( Si‐1 ) and into growing oligonucleotides ( Si‐1‐ODN ), as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Our preferred method is thermal hydrosilation of alkenyl/alkynyl derivatives due to its functional group tolerance 71. 72 Alkylation of hydrogen‐terminated Si<111> ( Si‐H ) with 4,4′‐dimethoxytrityl‐protected ω ‐undecenol provides modified silicon surfaces ( Si‐C 11 ‐ODMT ) which, after detritylation, present a primary alcohol group suitable for on‐chip DNA synthesis 5. As a phosphoramidite, 1 was incorporated at the electrode surface as a monomer ( Si‐1 ) and into growing oligonucleotides ( Si‐1‐ODN ), as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen‐terminated surfaces represent the initial state from which silicon semiconductor devices are fabricated 11. Chidsey and co‐workers first demonstrated that such single‐crystal surfaces12 react with alkenes to give chemically robust Si−C‐bonded monolayers, and further advances have shown the applicability of this chemistry to porous silicon 1315. The reaction may be driven by thermal, catalytic, electrochemical, and photochemical methods,13, 16 and patterning of the monolayers, for example, by using photolithographic techniques, is possible.…”
mentioning
confidence: 99%
“…The reaction may be driven by thermal, catalytic, electrochemical, and photochemical methods,13, 16 and patterning of the monolayers, for example, by using photolithographic techniques, is possible. We have used a simple protecting group method to produce monolayers with terminal OH groups (Figure 1); hydrogen‐terminated silicon surfaces of oriented (111) single‐crystal and porous silicon were alkylated with 4,4′‐dimethoxytrityl‐protected ω ‐undecenol (trityl=triphenylmethyl) by refluxing it in toluene; this is a previously established method to form robust Si−C‐bonded monolayers 15, 17. The 17‐mer oligonucleotides where then synthesized at these modified surfaces with UltraMILD base phosphoramidites (Glen Research, VA, USA) by using a DNA synthesizer and a column assembly modified to accept approximately 1‐cm 2 Si chips.…”
mentioning
confidence: 99%